2013
DOI: 10.1002/ca.22289
|View full text |Cite
|
Sign up to set email alerts
|

Clinical prevalence of palmaris longus agenesis: A systematic review and meta‐analysis

Abstract: We report a systematic review and a proportion meta-analysis of prevalence studies evaluating the prevalence of palmaris longus agenesis (PLA) in the literature. The overall PLA rate was defined to be the primary outcome. Secondary outcomes were rates of PLA in relation to ethnicity, laterality, side, gender, age, and hand dominance. We identified 26 articles which met the inclusion criteria. Meta-analyses showed an overall PLA pooled rate of 20.25%, higher than the commonly reported overall rate of 15%. Our r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 49 publications
(105 reference statements)
1
36
1
2
Order By: Relevance
“…However, the current predominant hypothesis is that early modern humans have a single origin from East Africa, where the rate of PLM agenesis is the lowest. 25 Whether the phylogenetic degeneration of PLM occurred after Homo sapiens migrated out of Africa into new geographic areas is a question still to be fully studied. Another hypothesis associates the low rate of absence of PLM in Africans with the high prevalence of manual labour.…”
Section: Discussionmentioning
confidence: 99%
“…However, the current predominant hypothesis is that early modern humans have a single origin from East Africa, where the rate of PLM agenesis is the lowest. 25 Whether the phylogenetic degeneration of PLM occurred after Homo sapiens migrated out of Africa into new geographic areas is a question still to be fully studied. Another hypothesis associates the low rate of absence of PLM in Africans with the high prevalence of manual labour.…”
Section: Discussionmentioning
confidence: 99%
“…During 2013, the focus still lies on case reports, cross sectional studies and narrative reviews even though we identified two articles which have been satisfactorily published and that incorporate a systematic review and metaanalysis of morphological literature for solving anatomical and/or clinical-surgical questions (Raikos & Paraskevas, 2013;Yammine, 2013). This supposes that medical tools based on evidence are now being considered by researchers in morphological sciences as valid instruments for problemsolving situations related to the field.…”
Section: To the Editormentioning
confidence: 99%
“…Al año 2013 el predominio sigue estando en las los reportes de caso, cortes transversales y revisiones narrativas, aunque vemos con satisfacción que han sido publicados dos artículos que incorporan una revisión sistemática y metaanálisis de literatura morfológica para resolver cuestionamientos anatómicos y de interés clínico-quirúrgico (Raikos & Paraskevas, 2013;Yammine, 2013), lo que supone que las herramientas de la medicina basada en evidencia comienzan a ser consideradas por los investigadores de las ciencias morfológicas como instrumentos válidos para resolver problemas de la disciplina.…”
Section: Señor Editorunclassified
“…It runs downwards and terminates in a long, slender tendon which passes anterior to the transverse carpal ligament, crosses the retinaculum, becomes flat and enters the palmar aponeurosis of the hand, anterior to the flexor retinaculum. Its innervation comes from branches of the median nerve [2]. The PL muscle flexes the wrist weakly as an accessory flexor muscle.…”
Section: Humberto Ferreira Arquez 1 Introductionmentioning
confidence: 99%
“…This role is due to its slender move over the long adaptor of the thumb. Generally, its role is negligible and this is the reason why it is lost in many operations without cost to the function of the forearm or the wrist [1][2][3].…”
Section: Humberto Ferreira Arquez 1 Introductionmentioning
confidence: 99%